Impact of Road Gradient on Fuel Consumption, Fuel Rate and CO₂ Emissions of Freight Transport - Abdul, Rahman; Hakzah, Hakzah; Andriyani, Andriyani; Jasman, Jasman; Kasmaida, Kasmaida (ASTONJADRO, 2026)
This study investigates the impact of road gradient on fuel consumption, fuel rate (FR), and CO₂ emissions in freight transport vehicles with two-axle and three-axle configurations. The research was conducted on a 250-meter road segment with a 0.067 rad (~7%) gradient in front of Taman Rekreasi Datae, Sidenreng Rappang Regency, South Sulawesi, Indonesia. A quantitative mathematical model, based on vehicle technical parameters and empirical formulations from previous studies, was applied. Results show that increasing the gradient from 0 to 0.067 rad raised fuel consumption in two-axle trucks from 0.0356 L to 0.0857 L and in three-axle trucks from 0.1463 L to 0.3269 L. The FR for two-axle trucks increased from 0.0014 L/s to 0.0056 L/s, while for three-axle trucks it rose from 0.0033 L/s to 0.0124 L/s. CO₂ emissions from two-axle trucks increased from 0.0958 kg to 0.3941 kg, and from 0.2310 kg to 0.8807 kg for three-axle trucks. The relative increase was higher for two-axle trucks (311%) than for three-axle trucks (281%), due to axle load distribution, engine capacity, and transmission ratio. These findings highlight the need to consider vehicle configuration and topography in route planning to minimize fuel consumption and emissions in hilly regions.